Adaptive Image Processing Algorithms for Printing - Safonov, Ilia V.; Kurilin, Ilya V.; Rychagov, Michael N.; Tolstaya, Ekaterina V.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents essential algorithms for the image processing pipeline of photo-printers and accompanying software tools, offering an exposition of multiple image enhancement algorithms, smart aspect-ratio changing techniques for borderless printing and approaches for non-standard printing modes. All the techniques described are content-adaptive and operate in an automatic mode thanks to machine learning reasoning or ingenious heuristics. The first part includes algorithms, for example, red-eye correction and compression artefacts reduction, that can be applied in any photo processing application, while the second part focuses specifically on printing devices, e.g. eco-friendly and anaglyph printing. The majority of the techniques presented have a low computational complexity because they were initially designed for integration in system-on-chip. The book reflects the authors' practical experience in algorithm development for industrial R&D.
Exposure Correction -- High Dynamic Range Imaging -- Image Processing using EXIF metadata -- Adaptive Sharpening -- Global and local noise reduction -- JPEG-artifacts detection and reduction -- Undesired artifact removal -- Red-eye correction -- Closed-Eye detection -- Image interpolation -- Panoramic images -- Smart cropping -- Still image retargeting -- Auto image rotation -- Anaglyph printing -- 3D printing.
Keywords: Signal processing; Computer vision; Signal, Speech and Image Processing; Computer Vision